Lyme disease and heart transplantation: presentation of a clinical case and a literature review - Pilypas, Audrius Aurelijus; Raišelienė, Giedrutė; Valaikienė, Jurgita (Acta medica Lituanica, 2020)
Background. Lyme disease, the most common anthropozoonosis, is a transmissible natural focal infection affecting various organs and systems. Also known as Lyme borreliosis, it is caused by Borrelia spirochetes, which are distributed by ticks of the genus Ixodes. Early diagnosis is difficult due to frequent occurrence of atypical symptoms, unnoticed tick bites, the absence of migratory erythematous lesions, and symptoms occurring during the nontick season. If not diagnosed and treated in time, dissemination of the infection occurs and various complications develop since borrelias damage not only the skin but also the nervous system, joints, and, in rare cases, the heart and eyes. Materials and methods. This article presents a clinical case of Lyme borreliosis-induced myocarditis, which led to the development of dilated cardiomyopathy and, consequently, urgent cardiac transplantation. According to our data, this is one of the first described cases of this complication in the world. Results and conclusions. When diagnosed in time and treated properly, the prognosis of Lyme myocarditis is usually good. In most cases, the atrioventricular block disappears within 1–2 weeks of antibiotic treatment and the implantation of a temporary pacemaker is rarely needed. In those rare cases of a chronic Borrelia burgdorferi infection, dilated cardiomyopathy may develop; thus if a sudden atrioventricular block occurs, the physician should be vigilant and perform the necessary tests to exclude the diagnosis of Lyme disease.
Keywords: Lyme myocarditis; atrioventricular block; Lyme disease; dilated cardiomyopathy